2016
DOI: 10.11648/j.ajss.20160403.11
|View full text |Cite
|
Sign up to set email alerts
|

Use of Energy Drinks Among College Students in Saudi Arabia

Abstract: Abstract:Energy drinks are popular among college students in Saudi Arabia (S.A) who consume these drinks for a variety of reasons. For example, college students believe that energy drinks can improve attention and/or reaction times during extended periods of cognitive demand. However, some of the ingredients in energy drinks, particularly sucrose and caffeine, can cause negative health effects such as an increase in heart rate and blood pressure and possible dehydration. In addition, these drinks can interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…Moreover, the University of New Hampshire reported that 79.9% of their students are coff ee drinkers [14] . On the other hand, we found the consumption of energy drinks in our population were relatively low (5%), which is contrary to the high consumption of energy drinks among college students that was reported in Saudi Arabia (71.6%), Th ailand (34%), and the USA (51%) [11,17,18] . Further, caff einated beverage consumption was signifi cantly higher in females than in males.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the University of New Hampshire reported that 79.9% of their students are coff ee drinkers [14] . On the other hand, we found the consumption of energy drinks in our population were relatively low (5%), which is contrary to the high consumption of energy drinks among college students that was reported in Saudi Arabia (71.6%), Th ailand (34%), and the USA (51%) [11,17,18] . Further, caff einated beverage consumption was signifi cantly higher in females than in males.…”
Section: Discussioncontrasting
confidence: 99%
“…About 33.4% of students at Taibah University declared regular consumption of energy drinks in 2018, whereas 52.2% of the students in a female secondary school had consumed EDs in 2011 (Katib et al, 2018;Aluqmany et al, 2013). An additional study in three universities in Saudi Arabia showed that about 70% of students regularly consumed EDs (Aljaloud, 2016). As for the ingredients, it must be mentioned that the main components of EDs are caffeine and carbohydrates; the content of caffeine is high and varies among the products of the different companies.…”
Section: Introductionmentioning
confidence: 99%
“…Energy drinks are very popular among our Saudi youth, but awareness of potential health hazards is limited. 56 , 57 We found that reduced parasympathetic drive and/or increased sympathetic outflow in females and particularly in OW/OB subject is further augmented by energy drinks. The VR is an effective, cheap and widely accepted method that can be conveniently used for the detection of autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 69%